2020
DOI: 10.1101/2020.07.22.215236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virus-free and live-cell visualizing SARS-CoV-2 cell entry for studies of neutralizing antibodies and compound inhibitors

Abstract: The ongoing COVID-19 pandemic, caused by SARS-CoV-2 infection, has resulted in hundreds of thousands of deaths. Cellular entry of SARS-CoV-2, which is mediated by the viral spike protein and host ACE2 receptor, is an essential target for the development of vaccines, therapeutic antibodies, and drugs. Using a mammalian cell expression system, we generated a recombinant fluorescent protein (Gamillus)-fused SARS-CoV-2 spike trimer (STG) to probe the viral entry process. In ACE2-expressing cells, we found that the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…Although site S4 is far from ACE2 binding site, corresponding mAbs P05-5B6 and P05-6H7 can neutralize SARS-CoV and SARS-CoV-2 infection without blocking S protein binding to ACE2, as reported S309 (47). Majority of potently neutralizing antibodies inhibit viral infection by blocking spike proteins attachment with receptors (53)(54)(55), however, we speculate that the site S4 directed mAbs may inhibit SARS-CoV-2 and SARS-CoV infection by intracellular neutralization pathway, a mechanism inhibiting the release of virus within endosome into cytoplasm, as reported in recent studies (40).…”
Section: Similar To Others Virus Infection An Increase In Mabs Binding Activity To Sars-supporting
confidence: 72%
See 1 more Smart Citation
“…Although site S4 is far from ACE2 binding site, corresponding mAbs P05-5B6 and P05-6H7 can neutralize SARS-CoV and SARS-CoV-2 infection without blocking S protein binding to ACE2, as reported S309 (47). Majority of potently neutralizing antibodies inhibit viral infection by blocking spike proteins attachment with receptors (53)(54)(55), however, we speculate that the site S4 directed mAbs may inhibit SARS-CoV-2 and SARS-CoV infection by intracellular neutralization pathway, a mechanism inhibiting the release of virus within endosome into cytoplasm, as reported in recent studies (40).…”
Section: Similar To Others Virus Infection An Increase In Mabs Binding Activity To Sars-supporting
confidence: 72%
“…To investigate whether blocking S protein binding to ACE2 is the key mechanism for NAbs to inhibit infection of SARS-CoV-2 into susceptible cells, such as lung cells and intestinal cells, mAbs were mixed with SARS-CoV-2 S protein at different concentrations and then added into 293T cells expressing human ACE2 to evaluate the capability of blocking S protein entrance into cells, as reported (40). The results showed that 61.0% of the specific mAbs had the ability to block entrance of S protein into cells, IC50 ranging from 4 ng/mL to 100 μg/mL (Fig.…”
Section: Characterization Of Sars-cov-2 Rbd-specific Mabs Obtained From Convalescent Covid-19 Individualsmentioning
confidence: 99%
“…SARS-CoV-2 Spike trimer fused to a constitutively fluorescent protein (Gamillus, isolated from Olindias formosus) has also been developed, providing a versatile tool for high-throughput screening and phenotypic characterization of SARS-CoV-2 entry inhibitors. 39 The Promega HiBiT/LgBiT ® system can be exploited for HiBiTtagged VNT (hiVNT): genome-free virus-like particles are incorporated with a small luciferase peptide (HiBiT) and their entry into…”
Section: Nonviral Alternativesmentioning
confidence: 99%
“…SARS‐CoV‐2 Spike trimer fused to a constitutively fluorescent protein (Gamillus, isolated from Olindias formosus ) has also been developed, providing a versatile tool for high‐throughput screening and phenotypic characterization of SARS‐CoV‐2 entry inhibitors 39 …”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that an actin-dependent receptor-HIV co-localization is essential for viral entry, which is potentially sensitive to cytochalasin D 19 . Furthermore, cytochalasin D was shown to prevent SARS-CoV-2 cell entry in a virus-free, live-cell assay 20 . Importantly, all identified HBV inhibitors show antiviral activities at non-toxic compound concentrations, indicating that no essential cellular house-keeping functions are critically disturbed.…”
Section: Discussionmentioning
confidence: 99%